Instrumen Analisis Hadith Sebagai Alat Pengukuran Isu Keselamatan Makanan Dalam PKS Sektor Perkhidmatan Makanan: Hadith Analysis Tool as Measurement Instrument for Food Safety Issues in the Food Service Sector SMEs - Md Ariffin, Mohd Farhan; Ahmad, Khadher; Man, Sa’adan (Online Journal of Research in Islamic Studies, 2018)
In the context of Malaysia, Small and Medium Enterprises (SMEs) are the industries that play an important role in the production of food products and consumables. SMEs are a large industry because involving large networks starting from the agricultural sector that supplies raw materials to the manufacturing sector for the purpose of producing products before being marketed to consumers. In other words, SMEs dominate the food industry in Malaysia. The question is, there is a tendency among SMEs to tolerate safety measures in the process of food preparation. The competitive environment between SMEs had an impact on the production of unsafe products. This, in turn, resulted in the presence of impurities, usage of prohibited chemicals or preservatives, the sale of expired items, reduction in the frequency of cleaning of food preparation premises and so on. As for implication, SMEs are the main medium for food safety issues. The findings show that there are eleven food safety issues which are the main problems among SMEs in Malaysia, namely the issue of physical contamination, chemical contamination issue, biological contamination issue, food workers issue, air pollution issue, water pollution issue, environmental pollution issue, animal pollution issue, public health issue, industrial processing issue and biotech issue in food. Of these, there are twenty-nine hadiths which focus on discussions on the food safety issues involved. In this study, Hazard Analysis Critical Control Point or HACCP is a standard that used as the framework of early measurement instrument on food safety issues. Finally, the study has developed hadith analysis tool in the form of a decision tree based on the HACCP framework as a current food safety procedure as an alternative step in addressing food safety issues in SMEs in Malaysia